The Fetus’s Rights Due to Pregnancy Abortion - Nurhayati,; Sofyan, Andi Muhammad; Sampurno, Slamet; Muchtar, Syamsuddin (International Journal of Psychosocial Rehabilitation, 2020)
The debate about abortion is still actual topic relating to assumption that the fetus could not be dropped for certain reasons, especially abortion for pregnancy due to rape. This research aims to determine arrangement about abortion in positive Indonesian law and to review protection rights of the fetus in conjunction with the legality of abortion on pregnancy due to rape. The method used is normative juridical using a statutory and concept approach . The results of this research that Indonesian positive law related to abortion in pregnancy due to rape is a limited of Rape. The right to the fetus's life in the womb is the nature rights which are owned as a gift from Almighty God that cannot be reduced by any reason and must be protected and respected by every person, society or country. The role of the country is very important in providing a guarantee of protection against the fetus's right to avoid abortion.Keywords-- , ,